SELF-SEEKING TOWARDS SELF-KNOWLEDGE IN THE CONFESSIONS’ BOOK WRITTEN BY SAINT AUGUSTINE - Abdul Muaz; Hanif Nurcholish Adiantika; Sarip Sarip (Fakultas Agama Islam Universitas Wiralodra, 2019)
This study aims to investigate Self-Seeking towards Self-Knowledge which plays an essential role for the life moment of the famous and distinguished Christian mystic namely Saint Augustine. He seeks and asks about himself as a human being, both horizontally [his relationship with another man], and vertically [his relationship with God the Creator]. He also reveals the answers toward his questions and searching. It can be explored in his masterpiece entitled ‘The Confession’. This study also relies on this book, as the primary reference, to explore and analyze Self-Seeking and Self-Knowledge in Western Mysticism. Therefore, the present study addresses research questions as follow: What is the definition of true Self-Seeking in general? What kind of Self-Knowledge offered by Saint Augustine inside the circumstance of the Western Mysticism Treasury? What is the significance of the Self-Seeking and the Self-Knowledge which is relevant with the current context?